Comparative Law for Legal Translation: Examining Nepali-English Translation - Bhattarai, Achyutananda (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This article examines the comparative law for legal translation to analyze the Nepali-English legal translation. It studies comparative law to find the nearest equivalence between the source and the target legal systems. The comparative laws are applied in Nepali legal translation to explore the semantic and procedural similarities and differences between two systems even if the effect is symmetrical. The equivalence between Nepali and English legal terminologies is analyzed at linguistic and extra linguistic levels using Eugene Nida’s equivalence theory and Mary Snell-Hornby’s cultural theory. The comparative study of law is used in legal translation to explore the sociocultural aspect of law which differs from system to system or nation to nation. In translating legal text some source law concepts do not correspond to the target legal system, which challenges legal translation to convey the source message to the target readers in their language and culture. The knowledge of comparative law works to overcome the challenges by analyzing the SL legal systems to find the nearest equivalence in the TL system. This research analyzes conceptual legal terms between Nepali and English to find similarities and differences in meaning and effect in translation. The significance of this study is to increase awareness of the comparative law for legal translation and increase translation competence. It concludes that the legal translator needs to know comparative law to comprehend source law properly and translate it into the target legal system. It helps to match the right equivalence and minimizes the risk of under-translation or over-translation.